A Modified Treatment Through Point-to-Point Coil Embolization for Direct Carotid Cavernous to Fistula: A Single-Center Result - Zhang, Zihuan; Liu, Jiaqiang; Zhang, Bingbing; Zhou, Mengliang; Zhao, Xintong; Li, Zhenbao (Frontiers in Neurology, 2021)
This study aims to assess the safety and efficacy of the modified treatment through point-to-point coil embolization of direct carotid cavernous fistula (dCCF), and evaluate the long-term outcome of patients who underwent the above treatment. A total of 18 patients who suffered from dCCF (a total of 19 fistulas) between January 2013 to May 2020 were analyzed. Among these patients, 14 patients were treated through point-to-point coil embolization of the fistula, while four patients were treated through combined endovascular embolization (coils, a balloon, Onyx, and/or a stent). The number of coils that filled the fistulas was counted. The primary outcome was defined by postoperative digital subtraction angiography (DSA) or the signs after the recanalization of dCCFs during the follow-up period. For patients with dCCF who underwent point-to-point coil embolization, a minimum of three coils and a maximum of 16 coils were used for these 14 fistula patients, and an average of 7.9 coils were used for each fistula, but none of the fistulas was recanalized. Furthermore, two pseudoaneurysms were observed as a result of the compression of the coils. However, none of these 14 patients presented with signs of recanalization of fistulas or cranial paralysis. The procedure applied for the present study was shown to be a safe, economical and efficacious treatment approach for dCCFs through the point-to-point coil embolization of the fistula.